The association between religious orientation and life satisfaction in older adults living with morbidity and multimorbidity: a gender perspective in Malaysia. Issue 6 (27th September 2020) - Foong, Hui F.; Hamid, Tengku A.; Ibrahim, Rahimah; Haron, Sharifah A.
Abstract : Background: Little is known about gender differences in the relationship between religious orientation and life satisfaction in older adults living with chronic disease(s). Therefore, the purpose of this article was to examine the moderating effect of gender on the association between religious orientation and life satisfaction in older adults living with morbidity and multimorbidity. Methods: The study involved 1790 community‐dwelling older adults aged 60 and above living with at least one chronic medical condition. The Satisfaction with Life Scale and Revised Intrinsic/Extrinsic Religious Orientation Scale were used to measure life satisfaction and religious orientation. Moderated hierarchical multiple regression was used to test the moderation effect. Results: Results showed that while intrinsic religiosity was positively associated with life satisfaction, extrinsic religiosity was found to have a negative relationship with life satisfaction. Gender moderated the association between intrinsic religiosity and life satisfaction. Conclusions: The findings suggested that the positive impact of intrinsic religiosity on life satisfaction was stronger in older women living with morbidity and multimorbidity. Healthcare practitioners can help disadvantaged older women in identifying their religious values and practices to improve their subjective wellbeing.